2022
DOI: 10.1101/2022.04.19.488840
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TubULAR: Tracking in toto deformations of dynamic tissues via constrained maps

Abstract: A common motif in biology is the arrangement of cells into tube-like sheets, which further transform into more complex forms. Traditionally, analysis of tissues’ dynamic surfaces has relied on inspecting static snapshots, live imaging of cross-sections, or tracking isolated cells in 3D. However, capturing the interplay between in-plane and out-of-plane behaviors requires following the full surface as it deforms and integrating cell-scale motions into collective, tissue-scale deformations. Here, we introduce an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 83 publications
0
22
0
Order By: Relevance
“…5A [28][29][30]. This process is known to be stereotyped across embryos, but the quantification of its dynamics has until recently proven elusive, due to the complex shapes and inherently 3D deformations [30,31]. Variability of the morphogenetic program between embryos remains largely uncharacterized [32].…”
Section: Morphodynamic Alignment Of a Shape-changing Visceral Organ R...mentioning
confidence: 99%
See 2 more Smart Citations
“…5A [28][29][30]. This process is known to be stereotyped across embryos, but the quantification of its dynamics has until recently proven elusive, due to the complex shapes and inherently 3D deformations [30,31]. Variability of the morphogenetic program between embryos remains largely uncharacterized [32].…”
Section: Morphodynamic Alignment Of a Shape-changing Visceral Organ R...mentioning
confidence: 99%
“… (A) The midgut envelops to the embryo’s yolk and folds into chambers ~ 13-15 hours post fertilization. Extracting the endodermal (inner) surface of the gut using TubULAR [31] yields collections of dynamic organ shapes. Scale bars are 100 μm.…”
Section: Morphodynamic Alignment Of a Shape-changing Visceral Organ R...mentioning
confidence: 99%
See 1 more Smart Citation
“… Automatic segmentation of the apical (inner) surface of the endoderm minimizes a non-local Chan-Vese energy functional ( Chan and Vese, 2001 ; Márquez-Neila et al, 2014 ) to encapsulate yolk without enclosing midgut tissue, shown for four snapshots of mid-sagittal sections using TubULAR ( Mitchell and Cislo, 2022 ). Blue contours mark the surface intersection with the mid-sagittal plane.…”
Section: Introductionmentioning
confidence: 99%
“… We compute the centerline (brown curve) for extracted shapes (green with purple boundary for clarity) using the TubULAR package ( Mitchell and Cislo, 2022 ). The cumulative length of these curves defines the effective length of the organ reported in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%